Dampak Set Peluang Investasi Terhadap Cost Of Equity Capital Pada Perusahaan Publik di Indonesia - Sri Hermuningsih (Conference In Business, Accounting, And Management (CBAM), 2012)
The purpose of this study demonstrate the influence of Investment Opportunity Set to Cost Of Equity Capital companies listed on the Indonesia Stock Exchange. The population in this study are all companies listed on the Indonesia Stock Exchange in the period 2008 to 2010. Sample selection by using purposive sampling number of 107 companies. Hypothesis testing by Structural Equation Model (SEM) These findings showed that the Investment Opportunity Set have a significant negative impact on Cost Of Equity CapitalKeywords: Set Peluang Investasi, Cost Of Equity Capital